Disease Characteristics of Chronic Venous Disease in Referral Hospital in Bangladesh (Medicine Today, 2023)
Introduction:Chronic venous disease (CVD) is widespread, underdiagnosed, and can progress to chronic venous insufficiency and venous ulcer, which can require extensive treatment. This condition negatively impacts patient quality of life and place substantial burdens on healthcare resources. In Bangladesh this problem is increasing with very poor awareness.Materials and Methods: The prospective observational study was carried out in department of vascular surgery of National Institute of Cardiovascular disease. We randomly choose 180 patients with chonic venous disease (CVD) and evaluate their characteristics and prevalence of several types. Data collection started from May 2021 for next 6 months.Results: : The patients of this survey were aged between 24 to 70 years and the Mean±SD age was 43.6±12.2. 78.3% of total study population were male, 33.3% were businessman and 10% were housewife. 66.6% patients were having low socio-economic condition. C2 varicose veins were highly prevalent among the study population (35%) & lowest prevalence of C4b lipodermatosclerosis or atrophie blanche (11.7%) we have seen in the study. (31- 40) & (51-60) these two age group were more prone to have CVD, 28.33% (n51) & 26.67% (n48) (p